The Influnce of Social Studies Student’s Learning Motivation and Wordwall use on Class IX Student Learning Outcomes - Ramadayanti Pulungan; Ripho Delzy Perkasa; Toni Nasution (STKIP Taman Siswa Bima, 2024)
The problem in this research is the lack of understanding regarding student learning motivation and the use of media in student learning which affects learning outcomes. Low motivation and the use of inappropriate methods can hinder students’ achievement of learning outcomes. This research aims to analyze and describe the extent of social studies learning motivation and the use of wordwalls on the learning outcomes of Class IX MTS Hifzhil Qur’an Medan students. This analysis uses a quasi-experimental quantitative method. The results of this research obtained a tcount of learning motivation of 2.409 with a ttable value of 2.000. The order is based on accepting Ha and rejecting Ho if tcount > ttable. So if the total learning motivation is 2,409 > 2,000 it means Ha is accepted and Ho is rejected. The results of the research obtained were that the t-count of learning outcomes for the group given the treatment and the group that was not given treatment was 7.337 with a t table value of 2.000. The order is based on accepting Ha and rejecting Ho if tcount > ttable. Then, the learning outcomes of the class given treatment and the class not given treatment used wordwall media with a total f count greater than f table, namely 4.349 > 3.16 and the significance value was 0.042 < 0.05, so Ha was accepted and Ho was rejected, meaning there was a significant influence between Use of Technology-Based Learning Media on Student Learning Outcomes in Class IX MTS Hifzhil Qur’an Medan.